/
/
/
Choose the one alternative that best completes the statement or answers the question. Simplify.
Not my Question
Flag Content

# Question : Choose the one alternative that best completes the statement or answers the question. Simplify. : 2152277

MULTIPLE CHOICE. Choose the one alternative that best completes the statement or answers the question.

Simplify.

1) ((2/a) + (7/b)/(1/x) - (1/y))

A) (xy(2a + 7b)/ab(x - y))

B) (7a + 2b/y - x)

C) (ab(7a + 2b)/xy(y - x))

D) (xy(7a + 2b)/ab(y - x))

2) ((2/x) + (9/y)/9x + 2y)

A) (9x + 2y/xy)

B) xy

C) (1/xy)

D) (2x + 9y/9x + 2y)

3) ((8/x)/(7/x) - (1/x2) )

A) (8x/7x - 1)

B) (7x - 1/8x)

C) (8x/7x + 1)

D) (8x2/7x2 - 1)

4) ((7/xy)/(4/x) + (5/y))

A) (5x + 4y/7)

B) (7/5x + 4y)

C) (7xy/5x + 4y)

D) (7/4x + 5y)

5) ((x/8) + (1/2)/(1/4x) - (9/8))

A) (x + 4/2 - 9x)

B) (x2 + 4x/9x + 2)

C) (x2 + 4x/1 - 9x)

D) (x2 + 4x/2 - 9x)

6) ((49t2 - 16s2/st) /(7/t) - (4/s))

A) 4s + 7t

B) (4s + 7t/st)

C) 7s + 4t

D) (st/7s + 4t)

7) (9 + (3/x)/(x/4) + (1/12))

A) (36/x)

B) 36

C) (x/36)

D) 1

8) ((7/x) + 1/(7/x) - 1)

A) 7 - x2

B) (7 + x/7 - x)

C) (x2/7 - x2)

D) 7

9) ((6/3x - 1) - 6/(6/3x - 1) + 6)

A) (3x/2 - 3x)

B) (2 - 3x/3x)

C) (2 - x/x)

D) (2 + 3x/3x)

10) ((3/x2 - 16)/(2/x + 4) + (3/x - 4))

A) (5x + 4/3)

B) (3/5x - 4)

C) (3/5x + 4)

D) 5x + 4

Solve and check.

11) (7/x) - (1/4) = (4/x)

A) x = -12

B) x = 12

C) x = -3

D) x = (4/7)

12) (34/x) = 5 - (1/x)

A) x = 7

B) x = 6

C) x = (34/5)

D) x = (5/33)

13) (5 - x/x) + (3/4) = (7/x)

A) x = Ö((29/20))

B) x = -8

C) x = 8

D) x = -4

14) (7/x - 1) = (6/x + 1)

A) x = - (2/13)

B) x = - 13

C) x = - 2

D) x = 13

15) (1/x) + (1/x - 4) = (x - 3/x - 4)

A) x = -4

B) x = -1

C) x = 4

D) x = 1

16) (5/x + 4) - (3/x - 4) = (4/x2 - 16)

A) x = 3Ö(3)

B) x = 18

C) x = -18

D) x = 36

17) (x/2x + 2) = (-2x/4x + 4) + (2x - 3/x + 1)

A) x = - (12/5)

B) x = -3

C) x = 3

D) x = (3/2)

18) (1/x + 7) + (2/x + 3) = (-4/x2 + 10x + 21)

A) x = -7

B) x = 3

C) No solution

D) x = 0

19) (x/x - 1) + 3 = (1/x - 1)

A) x = 0

B) x = 1

C) x = -1

D) No solution

20) (-1/x - 1) = (6/x - 2) - (-1/x2 - 3x + 2)

A) x = 2

B) No solution

C) x = 0

D) x = 1

21) (6x/x + 5) - (30/x - 5) = (6x2 + 150/x2 - 25)

A) x = 0

B) x = 5

C) x = -5

D) No solution

What value(s) are not allowable replacements for the variable x? Do not solve the equation.

22) (2x/x - 4) - (3x/x - 5) = (4/x2 - 9x + 20)

A) x = 4, x = 5

B) x = -4, x = -5

C) x = 5

D) x = 4

23) (2x/x + 4) - (3x/x + 3) = (4/x2 + 7x + 12)

A) x = -4

B) x = -3

C) x = 4, x = 3

D) x = -4, x = -3

## Solution 5 (1 Ratings )

Solved
Algebra 1 Year Ago 162 Views